Children's Care Pattern in The Formation of Islamic Morals in The Divorce Family - Claudia Shabrina Pangestu; Noor Amirudin (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
This study aims to determine the condition of parents who experienced divorce in Randuagung Village, Kebomas District, Gresik Regency, East Java and to determine the importance of Islamic parenting for children in divorced families. This research is expected to provide good learning benefits for divorced parents in educating their children well, as well as providing additional knowledge for education practitioners to pay attention to the personality development of divorced family children. Parenting patterns (parenting patterns) are how the efforts of parents and extended families to interact in providing good role models, using attention, direction, and examples of wisdom characters, in order to prepare skills, morals, and children's personalities towards a more positive direction. The research approach used is field research. This research uses a descriptive qualitative approach. The target of this research is the condition and parenting style of the divorced family in Randuagung Village. The results of this study of 3 informants, in the parenting patterns of divorced families, there are 3 types of parenting styles, namely: acceptance, permissiveness, and rejection. Acceptance of parenting for divorced families due to economic reasons and domestic violence, emphasizes good manners, enthusiasm for learning, patience and understanding of the current situation, as well as being devoted to parents and their families. Whereas parenting with permissiveness from divorced families because of the economy and the treatment of the husband is immature, resulting in the ability to socialize with friends well (not insecure) willing to participate in worship (praying and reciting the Koran in the mosque). The rejection of parenting for divorced families for economic reasons, results in children becoming ignorant or indifferent to their lives.